Stroke in women — from evidence to inequalities - Cordonnier, Charlotte; Sprigg, Nikola; Sandset, Else Charlotte; Pavlovic, Aleksandra; Sunnerhagen, Katharina S.; Caso, Valeria; Christensen, Hanne (Nature Publishing Group, 2017)
Stroke is the second largest cause of disability-adjusted life-years lost worldwide. The prevalence of stroke in women is predicted to rise rapidly, owing to the increasing average age of the global female population. Vascular risk factors differ between women and men in terms of prevalence, and evidence increasingly supports the clinical importance of sex differences in stroke. The influence of some risk factors for stroke — including diabetes mellitus and atrial fibrillation — are stronger in women, and hypertensive disorders of pregnancy also affect the risk of stroke decades after pregnancy. However, in an era of evidence-based medicine, women are notably under-represented in clinical trials — despite governmental actions highlighting the need to include both men and women in clinical trials — resulting in a reduced generalizability of study results to women. The aim of this Review is to highlight new insights into specificities of stroke in women, to plan future research priorities, and to influence public health policies to decrease the worldwide burden of stroke in women.